An Exploration of Consumer Perceptions of Plants and Plant Characteristics: A Qualitative Study of Florida Plant and Garden Consumers - Kathryn Wilson; Carly Barnes; Tracy Irani (Journal of Applied Communications, 2013)
When planning and developing a state-specific agricultural product brand and marketing campaign, it is important to consider potential consumers’ perceptions of terminology, messages, and attitudes toward the product. This qualitative study explores Florida consumer perceptions of green industry terminology, such as “plant,” “garden,” “landscape,” and “home landscape” as well as plant characteristics important to consumer purchase. Participants in all six of the Florida-based focus groups utilized in this study did not feel that a brand was important to plant purchase. Given the findings in of the study, recommendations for marketing an agricultural product of this nature include using the word “plant” over “garden;” achieving the plant characteristics deemed to be the most important to plant purchases (healthy-looking, quality, and “makes me feel good’) with the product; and emphasizing these characteristics in a well-targeted marketing campaign.
Keywords: Florida gardening; Florida plant/garden consumers; branding; plant characteristics